Presence of music elements in teaching Spanish as a foreign language - Maričić Mesarović, Sanja; Матовић, Мирјана (Studies in Teaching and Education, 2024)
This article aims to analyze the presence of musical elements as well as the importance of the use of music in the process of learning a foreign language (FL) with a focus on the teaching Spanish as a foreign language at the Faculty of Philosophy of the University of Novi Sad (FFUNS). Music and language have numerous common characteristics that are recognizable through rhythm, melody, intonation, dynamics and represent a form of continuous mutual communication. Music stimulates the activity of the right hemisphere of the brain, thus encouraging creativity and imagination as key motivators in the learning process. In foreign language teaching, music can provide lexical and cultural input. Our research deals with the analysis of the presence of elements related to music in the textbooks used in the teaching Spanish as a foreign language at FFUNS. The quantitative analysis of the corpus identified examples that represent musical content or refer to musical elements within the teaching. The aim of this research is to identify which musical content is present in the textbooks and at what level of learning Spanish as a FL (A1-B2) and which language competences and skills develop with the help of found content. This research has confirmed that musical content can be used for the purpose of practicing and improving language skills, and for the purpose of developing and enriching students’ lexical, grammatical and intercultural competence.